Prioritizing Online Learning Platforms Based on Student Needs: A TOPSIS Analysis - Enos Lolang; Muthia Mutmainnah; Hafni Hafsah; Iwan Adhicandra; Ernie C Avila; Rahim, Robbi (Journal of Applied Science, Engineering, Technology, and Education, 2023)
The proliferation of online learning platforms has made it increasingly difficult for students to choose a platform that best meets their needs. This study aims to prioritize online learning platforms based on student needs using the Multiple Criteria Decision Analysis (MCDA) Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The criteria used in the analysis were ease of use, variety of courses, cost, and reputation of instructors. The results of the analysis indicate that edX is the most suitable online learning platform for students based on the criteria and weights used in the study. Coursera, Udemy, and LinkedIn Learning were also evaluated in the analysis and may be suitable for students with specific priorities or preferences. The MCDA TOPSIS method provides a transparent and objective approach to evaluating the alternatives and offers insights into the strengths and weaknesses of each platform. The results of this study can help students make more informed decisions and choose a platform that best meets their individual needs. However, the choice of criteria and weights may vary depending on the preferences and priorities of different students, and the results should be interpreted accordingly